EXPLORING BUSINESS MODEL DEVELOPMENT: APPROACHES, STRATEGIES, AND CHALLENGES - KANOVA, Oleksandra; KRYVOBOK, Kateryna; MYRONOVA, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is dedicated to exploring various strategies and approaches to business model development, emphasizing its role in enhancing organizational adaptability, competitiveness, and long-term sustainability. The study highlights the importance of business model development, innovation, and improvement in achieving sustainable success for organizations in dynamic market conditions. It identifies key factors that drive the need for continuous innovation of business models, including the impact of the external environment, influenced by rapid technological innovations, changing consumer preferences, economic volatility, and increasing competition. The article characterizes the main approaches to business model innovation depending on the enterprise’s strategic focus (counteracting downturns or negative industry changes or striving for breakthrough growth) and the direction of transformation (transforming the core business activity or extending beyond it). Based on these approaches, enterprises are divided into reinventors, mavericks, adapters, and adventurers. We examine the forms of business model innovation: startups, transformation, diversification, and acquisitions, each involving different degrees of change to the business model. Criteria for classifying a business model innovation as sustainable or contributing to sustainable development are outlined. Popular strategies for business model innovation are summarized: integration, replacement, expansion, separation, exclusion, optimization, and relocation. For each strategy, opportunities and challenges are identified. Typical directions for business model development through these strategies are outlined. Internal and external factors to be considered in the analysis preceding business model innovation are defined. The article emphasizes that sustainable business models integrate technological, social, and environmental factors to ensure long-term success. Innovations toward sustainable development are key to achieving economic success and a positive societal impact.